Augustine of Hippo, Servus Servorum Christi - Beaver, R. Pierce (Church history, 1934)
The age of Saint Augustine was for the episcopate of the West a period of training for future duties. Before the end of the fifth century, in almost every community the real leader, both in temporal and spiritual matters, was the bishop. During the next two centuries there came into being the medieval prelate, a prince in the church and in the state; but the foundations of his ecclesiastical and civil jurisdiction had already been laid by the early part of the fifth century. The African bishops shared with their colleagues of the other western provinces the same line of evolution, until it was interrupted, first by the Vandal invasion, and then by the Islamic conquest. However, by that time Augustine of Hippo, Alypius of Thagaste, the primate Aurelius of Carthage, and their fellow-bishops had made contributions of permanent value to the whole church, and they had created a noble standard of duty and conduct to be emulated by prelates of a later day.